Higher Body Mass Index is Associated with Increased Oxidative Stress in Patients of Type 2 Diabetes Mellitus - Edelbert A. Almeida; Mohit Mehndiratta; Sri V. Madhu; Rajarshi Kar (Indian Journal of Endocrinology and Metabolism)
Introduction: Type 2 diabetes mellitus (T2DM) is closely associated with the obesity; however, certain proportion of T2DM patients is non-obese or lean (BMI < 18.5 kg/m2). Obesity has long been associated with oxidative stress; however, there are no studies available documenting levels of oxidative stress in the lean patients of T2DM. Therefore, this study was done to compare the levels of makers of oxidative stress (TL, mtDNA, TAS) and their regulators (mRNA expression of TERT, Nrf2 and Nqo1) in lean and obese patients of T2DM. Methods: 60 newly diagnosed patients (treatment naïve) of T2DM were recruited and divided into lean (BMI < 18.5 kg/m2) and obese (BMI > 25 kg/m2) groups. Relative telomere length (T/S) and mtDNA content were estimated via real-time PCR. Serum total antioxidant status (TAS) was measured using a commercially available kit. mRNA expression of TERT, Nrf2 and Nqo1 was measured by real-time PCR. Results: Mean T/S and mtDNA content were lower in the obese group compared to the lean group (P = 0.16 and P = 0.06, respectively). Mean serum TAS levels were higher in obese group compared to the lean group (P = 0.001). mRNA expression of TERT and Nrf2 was increased in obese group compared to the lean group. mRNA expression of Nqo1 was similar in both the groups. Conclusion: Obese patients of T2DM are exposed to a greater degree of OS compared to the lean patients of T2DM.